2009
DOI: 10.1123/ijspp.4.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Cadence Choice During Submaximal Cycling and Cadence Influence on Performance

Abstract: Cadence choice during cycling has been of considerable interest among cyclists, coaches, and researchers for nearly 100 years. The present review examines and summarizes the current knowledge of factors affecting the freely chosen cadence during submaximal cycling and of the influence of cadence choice on performance. In addition, suggestions for future research are given along with scientifically based, practical recommendations for those involved in cycling. Within the past 10 years, a number of papers have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Similar to what seems to be the case for the most eYcient cadence one may expect an increase in FCC with increasing power output or velocity. Some studies indeed provide some circumstantial evidence for an increase during free cycling (FC) at treadmills or road cycling (e.g., Hansen et al 2002a, b;Ebert et al 2006;Vogt et al 2008;Hansen and Smith 2009;Sassi et al 2009). However, other studies report FCC not to change with power output in highly trained cyclists during ergometer cycling (EC) (Marsh et al 2000a, b;Sarre et al 2003;Hansen et al 2007;Hansen and Ohnstad 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Similar to what seems to be the case for the most eYcient cadence one may expect an increase in FCC with increasing power output or velocity. Some studies indeed provide some circumstantial evidence for an increase during free cycling (FC) at treadmills or road cycling (e.g., Hansen et al 2002a, b;Ebert et al 2006;Vogt et al 2008;Hansen and Smith 2009;Sassi et al 2009). However, other studies report FCC not to change with power output in highly trained cyclists during ergometer cycling (EC) (Marsh et al 2000a, b;Sarre et al 2003;Hansen et al 2007;Hansen and Ohnstad 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Several experimental studies have indicated that the freely chosen cadence (FCC) increases with increasing power output, as summarized in the review of Hansen and Smith (2009). Assuming that cyclists choose a cadence near to C opt , then C opt should also increase with increasing power output.…”
Section: Modelmentioning
confidence: 99%
“…To achieve a certain cycling velocity, a cyclist can either choose a high cadence and exert a low force on the pedals, or choose a low cadence and exert a high force on the pedals. Hence, cadence selection is a never-ending discussion in the theory and practice of cycling (Hansen et al 2002a(Hansen et al , b, 2006(Hansen et al , 2007Hansen and Smith 2009;Harnish et al 2007;Hausswirth et al 2009;Leirdal and Ettema 2009;Vercruyssen and Brisswalter 2009;Whitty et al 2009). Accordingly, the scientific community has examined the influence of cadence on several variables during cycling to identify an optimal cadence.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, training at different cadences seems to be important to set new stimuli for the same power output in trained cyclists. For higher exercise economy, road cyclists should choose a low cadence of 60 rpm [5][6][7]. However, in practice cyclists perform best at high (90 rpm) to very high (110 rpm) cadences [8].…”
Section: Introductionmentioning
confidence: 99%